Reduced transcription of the ferredoxin gene in metronidazole-resistant Trichomonas vaginalis. - Quon, D V (1992)
Metronidazole [1-(2-hydroxyethyl)-2-methyl-5-nitroimidazole] is used to treat infections caused by Trichomonas vaginalis, a sexually transmitted human parasite. This drug is administered in an inactive form and is reduced to its cytotoxic form within the hydrogenosome, an unusual organelle found in trichomonads. Metronidazole reduction occurs via ferredoxin-mediated electron transport. We have investigated the role of ferredoxin in metronidazole resistance. Immunoblot analysis of drug-resistant and -sensitive T. vaginalis strains shows that intracellular levels of ferredoxin are invariably reduced in the resistant strains relative to a sensitive strain. Similarly, Northern blot analysis shows that ferredoxin mRNA levels are reduced 50-65% in resistant strains. Using nuclear run-on assays, we show that ferredoxin gene transcription is reduced 40-65% in resistant strains. Sequence comparison of the region 5' of the ferredoxin gene among drug-sensitive and -resistant strains reveals two point mutations, at -178 and -239 nucleotides relative to the start of transcription, in a resistant strain. Interestingly, a protein of approximately 23 kDa binds to a 28-base-pair region that encompasses the mutation at -239 nucleotides. The binding affinity of this protein appears to be reduced in the mutant. These data strongly correlate drug resistance with altered regulation of ferredoxin gene transcription. A reduction in gene transcription results in decreased intracellular levels of ferredoxin. This, in turn, may play a role in metronidazole resistance by decreasing the ability of the cell to activate the drug.